Kauman Cultural Village: The Transformation of Cultural Tourism Towards an Inclusive Attraction - Kusumantoro; Lola Kurnia Pitaloka; Iva Sofi Gunawati (DEVOTIONIS, 2025)
Kauman Village in Kudus Regency has great potential for cultural tourism, but it still faces several challenges, particularly in terms of inclusivity and diversification of tourist attractions. The development of culture-based tourism in this village is crucial for boosting the local economy and attracting more visitors. Through the Participatory Rural Appraisal (PRA) method, this service explored local cultural potentials such as traditional games. The program successfully involved the community in tourism development, raising awareness of cultural potential, and creating new business opportunities. The successful revitalization of traditional games such as jumping rope, egrang bambu, and gobak sodor has attracted tourists and strengthened Kauman Village's identity as an inclusive cultural tourism destination. The service results show that a participatory approach and proper cultural promotion can significantly enhance tourism appeal and economic impact for the local community.